Al-Dirāsat al-Tahlīliyyah Li Muhtawā al-Kitāb al-Madrasiy Li Ta’līm al-Lughat al-‘Arabiyyah Fī al-Marhalah al-Tsānawiyyah al-‘Ammah ‘alā Asāsi CEFR (al-Ithār al-Marja’iy al-Aurubiy al-Musytarak) - Arif Taufikurrohman; Imam Asrori; Abdul Wahab Rosyidi (Lisanudhad: Jurnal Bahasa, Pembelajaran dan Sastra Arab, 2022)
Knowing the level of content of Arabic textbooks at the high school level is important because it is the starting point in preparing Arabic teaching materials at the university level. Without knowing the level, repetition can occur in determining the level and cause delays in increasing the linguistic level to a higher level. The purpose of this study was to analyze the description of the content of textbooks at the general secondary level based on the Common European Terms of Reference. In writing this research, the researcher used a descriptive approach to describe the contents of the book, analyzed it and then measured it based on the Common European Framework of Reference (CEFR) to determine the language level of this textbook. In this study, the researcher achieved the following results: First, the contents of the first textbook at the general secondary level for the tenth semester were at levels A1, A2, B1, and secondly that the second and third books echoed between two levels, namely: B1 and B2 language level.